Exercise Videogames, Physical Activity, and Health: Wii Heart Fitness: A Randomized Clinical Trial - Bock, Beth C. (Am J Prev Med, 2019)
INTRODUCTION: Adults who engage in regular physical activity have lower rates of morbidity and mortality than those who do not. Exercise videogames may offer an attractive, sustainable alternative or supplement to traditional modes of exercise. This study compared exercise videogames with standard exercise modalities for improving uptake and maintenance of moderate to vigorous physical activity, and health risk indices. STUDY DESIGN: A three-arm clinical RCT including 12 weeks of supervised laboratory-based moderate to vigorous physical activity followed by 6 months follow-up. SETTING/PARTICIPANTS: This study was conducted at a university affiliated hospital research lab. Healthy, sedentary adults were eligible. INTERVENTIONS: This study compared a 12-week program of supervised exercise videogames versus standard exercise (e.g., treadmill) versus control. Data were collected from January 2012 to September 2017 and analyzed in 2018. MAIN OUTCOME MEASURES: The primary outcome was weekly minutes of moderate to vigorous physical activity at end of treatment, assessed at 3 and 6 months post-intervention by using self-report and accelerometer data. Health risk indices (e.g., HbA1c, lipids) were also assessed. RESULTS: Participants (N=283) had an average age of 46.2 ±13.5 years; 79% were female. At end of treatment, those in the exercise videogame arm engaged in 30 minutes/week more moderate to vigorous physical activity compared with standard exercise and 85 more minutes/week than controls (all p<0.05). Exercise videogame participants had greater reductions in cholesterol, HbA1c, and body fat versus other groups. Reductions in cholesterol were twice as large in exercise videogame versus standard participants. CONCLUSIONS: Exercise videogames produced greater uptake and maintenance of moderate to vigorous physical activity compared with standard exercise and improvements in multiple health risk indices. Exercise videogames may promote sustainable physical activity with significant health benefits. TRIAL REGISTRATION: This study is registered at www.clinicaltrials.gov NCT03298919.